Entre libéralisme et progressisme : l’influence d’Adolphe Prins (1845-1919) dans la théorisation de la défense sociale et la construction de la protection de l’enfance en Belgique - Sylvain Wagnon (Criminocorpus)
Adolphe Prins was an acamedic, criminal lawyer, criminologist, inspector general of prisons, who was the initiator of judicial reforms on child protection. More generally, he was influential in the transformation of Belgian criminal law between the late nineteenth and early twentieth centuries. Although he was a theoretician of social defense policy, his influence on the legal development of the childhood’s protection and especilly in education, remains little-known. This article attempts to analyze the influence of Adolphe Prins in the development of the legal base of the social defense policy but also the role he played on the construction of child’s protection in Belgium. Three complementary approaches are discussed: depicting a singular trace route in Belgium in the contex of the industrial revolution of the nineteenth century, defining the Prins’ social defense thought and establishing the influence of Prins on the education reformers.